2008
DOI: 10.1111/j.1541-0072.2008.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment or Placebo: Are State Programs Decreasing the Proportion of Uninsured?

Abstract: Currently there are over 45 million Americans without health insurance. Recent growth in Medicaid and State Children's Health Insurance Program (SCHIP) enrollment of children has filled in the sizable gap created by decreased employer‐sponsored insurance since 2000. While the share of children who are uninsured actually decreased between 2000 and 2003, little progress was made in expanding public insurance to adults. As a result, advocates and policymakers at the federal and state level are searching for appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This study seeks to examine the effects of greater state effort with regard to market-based health policy efforts on selected indicators and does not seek to disentangle these effects from those of state-based programs. Prior research (Bernick and Myers 2008) found that the effects of tax incentives and even state-based direct coverage programs were obscured by the effects of Medicaid, still the major force for health insurance provision in the states. Thus, this study sought to test for the effects of market-based programs in the absence of these other programs.…”
Section: Discussionmentioning
confidence: 99%
“…This study seeks to examine the effects of greater state effort with regard to market-based health policy efforts on selected indicators and does not seek to disentangle these effects from those of state-based programs. Prior research (Bernick and Myers 2008) found that the effects of tax incentives and even state-based direct coverage programs were obscured by the effects of Medicaid, still the major force for health insurance provision in the states. Thus, this study sought to test for the effects of market-based programs in the absence of these other programs.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the uninsured population among the states may affect states’ choices to expand Medicaid. Medicaid expansions were the sole effective tool used by states to increase health insurance coverage in the aftermath of the Clinton health reforms (Barrilleaux and Brace 2007; Bernick and Myers 2008; Kail, Quadagno, and Dixon 2009), but only a handful of states with the most generous prior Medicaid policies used that approach to reducing uninsurance. Thus, Medicaid expansion is a policy tool that has proved to work well in reducing the numbers of uninsured in the states.…”
Section: Why Might Governors Refuse the Obamacare Medicaid Expansion?mentioning
confidence: 99%
“…Two recent studies provide mixed support for the effectiveness of state reforms. Bernick and Myers (2008) suggest that neither tax incentives nor direct coverage programs are particularly effective at addressing the insurance problem and that states that adopt tax incentives may even increase the number of uninsured. Kail, Quadagno, and Dixon (2009) demonstrate that waivers for Medicaid and SCHIP programs, which allow states to expand coverage to targeted populations, are the only reforms that significantly increase coverage.…”
Section: Research On State Health Insurance Coveragementioning
confidence: 99%
“…Another reason for the difference in party effects may be the preferred policy approaches. Republicans typically like to rely on the private sector, which makes tax incentives for insurance coverage a more appealing option, but, as Bernick and Myers (2008) show, these incentives seem to be ineffective and may even increase the uninsured population. Lastly, Grogan (1994) finds that Republican control reduces eligibility for health insurance, which is inversely related to the possible expansion of coverage.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
See 1 more Smart Citation